2019
DOI: 10.6004/jnccn.2019.7308
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mismatch Repair Status Between Primary and Matched Metastatic Sites in Patients With Colorectal Cancer

Abstract: Background: Differences between the features of primary cancer and matched metastatic cancer have recently drawn attention in research. This study investigated the concordance in microsatellite instability (MSI) and mismatch repair (MMR) status between primary and corresponding metastatic colorectal cancer (CRC). Methods: Consecutive patients with metastatic CRC who had both primary and metastatic tumors diagnosed at our institution in January 2008 through December 2016 were identified. Immunohistochemistry wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…Previous literature showed that MSI-H and MSS cell populations may co-exist within the same MSI-H tumor and patients burdened with multiple tumors could also have discrete genotypes in different lesions, both of which are expected to be better captured by liquid biopsy. [37][38][39][40][41] Temporal Open access discordance may also have played a role since a previous study showed that tissue-blood concordance dropped from 100% to 60% as the time interval between tissue biopsy and blood draw increased from ≤2 weeks to >6 months. 42 The feasibility of predicting ICB efficacy by NGSdetermined bMSI has been explored previously.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature showed that MSI-H and MSS cell populations may co-exist within the same MSI-H tumor and patients burdened with multiple tumors could also have discrete genotypes in different lesions, both of which are expected to be better captured by liquid biopsy. [37][38][39][40][41] Temporal Open access discordance may also have played a role since a previous study showed that tissue-blood concordance dropped from 100% to 60% as the time interval between tissue biopsy and blood draw increased from ≤2 weeks to >6 months. 42 The feasibility of predicting ICB efficacy by NGSdetermined bMSI has been explored previously.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviation: P, prospective study; R, retrospective study; PD-1, programmed death-1; PD-L1, programmed death ligand 1; PD-L2, programmed death ligand 2; TIL, tumor-infiltrating lymphocyte; TMB, tumor mutational burden; MSI, microsatellite instability; NA, not available. [24,31,32,[79][80][81] conversion between primary lesions and paired metastases. Nine different cancer types were considered among all eligible studies in this analysis, including fifteen for the non-small cell lung cancer, fourteen for breast cancer, nine for colorectal cancer, five for the kidney renal clear cell carcinoma, five for the head and neck squamous cell carcinoma, four for bladder cancer, two for melanoma, one for synovial sarcoma and one for cervical cancer.…”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…Inconsistent TIL counts were reported in breast and lung tumours compared with their metastases [20,30]. High concordance of MSI status is found in primary colorectal cancers and their matched liver, lung, and distant lymph node metastases with a total incidence of 2À16% [31,32]. Although discordant status of these biomarkers between primary and metastatic sites has been extensively reported, results from different studies are yet controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In most tumors, the MSS status was identified in both primary and metastatic specimens, whereas among 46 primary MSI tumors, nine of them were classified as MSS when the metastatic lesion was tested. Interestingly, the discrepancy was mainly limited to peritoneal and ovarian metastases [ 242 ]. If MMR heterogeneity is now confirmed, the implications of this phenomenon in cancer progression and response to therapies are still unclear and need to be thoroughly investigated.…”
Section: Genetic Mechanisms Of Immune Evasion In Msi Crcmentioning
confidence: 99%